COVID-19 in Jordan: Impacts on Production, Household Income & Food Systems - Elsabbagh, Dalia; Raouf, Mariam; Wiebelt, Manfred (2021)
Prepared by Dalia Elsabbagh1, Mariam Raouf1, Manfred Wiebelt2 1. International Food Policy Research Institute 2. Kiel Institute for the World Economy Last updated: 2 September 2020